2012
DOI: 10.1111/j.1440-1797.2011.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium loading in normotensive healthy volunteers does not increase arterial vascular reactivity or blood pressure

Abstract: Dietary salt loading did not produce significant increases in PWV and blood pressure in normotensive subjects with systolic blood pressure <130 mmHg. The lack of an observed effect supports Guyton's pressure-natriuresis hypothesis with appropriate renal excretion of the excess sodium load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
(45 reference statements)
1
40
1
1
Order By: Relevance
“…Our study showed no change in PWV c-f between meals; however, we saw a small but significant trend for increased PWV c-f over time. Previous studies showed an improvement in fasting PWV c-f in hypertensive (10,33,34) but not normotensive (35) populations with reduced sodium intake. The influence of potassium on vascular function measures is unclear, with BP likely to influence any observed effect (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed no change in PWV c-f between meals; however, we saw a small but significant trend for increased PWV c-f over time. Previous studies showed an improvement in fasting PWV c-f in hypertensive (10,33,34) but not normotensive (35) populations with reduced sodium intake. The influence of potassium on vascular function measures is unclear, with BP likely to influence any observed effect (14).…”
Section: Discussionmentioning
confidence: 99%
“…17 Limited studies have examined the effects of sodium or potassium on measures of arterial stiffness, with inconclusive results both for sodium [18][19][20][21][22][23][24][25] and potassium. [26][27][28][29] We performed a randomised, placebo-controlled, crossover study to examine the effects of sodium and potassium supplementation on office BP, ambulatory BP and arterial stiffness in Dutch subjects with untreated elevated BP.…”
Section: Introductionmentioning
confidence: 97%
“…Intervention studies looking at the effect of sodium on PWV have shown that in normotensive populations, sodium supplementation/a high-sodium diet for 2-6 weeks has no effect on PWV [29,30,31]. In hypertensive populations, a high-sodium diet (>90 mmol/24 h) compared to a lower sodium intake increases PWV [32,33,34].…”
Section: Dietary Intake and Pwvmentioning
confidence: 99%